Los Petroglifos (Petro-grabados) del semidesierto de Coahuila, mensajes para las culturas visuales contemporáneas: Análisis desde la Semiótica para el diseño y la comunicación - Reyes Chavez, Enrique (UNIVERSIDAD DE SONORA, 2022)
The petroglyphs of Coahuila, found in the municipalities of Viesca, Parras de la Fuente and General Cepeda, constitute a true design of visual codes for intercommunication between the prehistoric inhabitants of the semi-desert area of ​​what today constitutes the extension of this State. They do not represent a mere artistic design as previously thought, but true complex and diverse codes among their neat inhabitants, elaborated sequentially from the primitive populations through time to the present, which today constitute true messages for contemporary visual cultures, since The function of the sign is to communicate ideas through messages (Guiraud, 2006). Unraveling its meaning is the task of experts in paleontology and archeology, so our contribution is only from an anthropological, semiological and communicative approach and reflection, focused on the theory of human communication (Watzlawick, 1991) and the semiology that highlights its characteristic of being substitutes for language from its particularity as paralinguistic logical codes, since they do not depend on articulated language and are autonomous and independent codes; that is, true and apparent silent witnesses of visual communication. This research is carried out from the Academic Body "Visual Expression", of the School of Plastic Arts of the Autonomous University of Coahuila, and the line of research "Image, communication and culture", reflections on multiculturalism and worldview, in addition to the social interactions in primitive communities and their communicating purposes.